Large-scale patterns of benthic marine communities in the Brazilian Province. - Anaide W Aued; Franz Smith; Juan P Quimbayo; Davi V Cândido; Guilherme O Longo; Carlos E L Ferreira; Jon D Witman; Sergio R Floeter; Bárbara Segal (PLoS ONE)
As marine ecosystems are influenced by global and regional processes, standardized information on community structure has become crucial for assessing broad-scale responses to natural and anthropogenic disturbances. Extensive biogeographic provinces, such as the Brazilian Province in the southwest Atlantic, present numerous theoretical and methodological challenges for understanding community patterns on a macroecological scale. In particular, the Brazilian Province is composed of a complex system of heterogeneous reefs and a few offshore islands, with contrasting histories and geophysical-chemical environments. Despite the large extent of the Brazilian Province (almost 8,000 kilometers), most studies of shallow benthic communities are qualitative surveys and/or have been geographically restricted. We quantified community structure of shallow reef habitats from 0° to 27°S latitude using a standard photographic quadrat technique. Percent cover data indicated that benthic communities of Brazilian reefs were dominated by algal turfs and frondose macroalgae, with low percent cover of reef-building corals. Community composition differed significantly among localities, mostly because of their macroalgal abundance, despite reef type or geographic region, with no evident latitudinal pattern. Benthic diversity was lower in the tropics, contrary to the general latitudinal diversity gradient pattern. Richness peaked at mid-latitudes, between 20°S to 23°S, where it was ~3.5-fold higher than localities with the lowest richness. This study provides the first large-scale description of benthic communities along the southwestern Atlantic, providing a baseline for macroecological comparisons and evaluation of future impacts. Moreover, the new understanding of richness distribution along Brazilian reefs will contribute to conservation planning efforts, such as management strategies and the spatial prioritization for the creation of new marine protected areas.